Pharmacological Activity and Mechanism of Action of Flavonoids from Diverse Millettia Plant Organs - Le Doux Kamto, Eutrophe; Kamdem, Boniface P. (Natural Products Journal, The, 2022)
Background: There has been increasing interest in the research of flavonoids from plant sources because of their versatile effects reported in various biological studies. The bioavailability, metabolism, and biological activity of flavonoids depend on the configuration, the total number of hydroxyl groups, and the substitution of functional groups about their nuclear structure. Plant organs are the main dietary source of flavonoids for humans and have been used as a remedy in traditional medicine. Some examples include Millettia plants which have been reported to contain several flavonoids with pharmacological activity against multifactorial diseases. Aim of the Study: The present study summarizes up-to-date and comprehensive information on the pharmacological activity of flavonoids from plants of the genus Millettia. Methods: The literature information was obtained from published and unpublished materials (theses, dissertations, and textbooks), retrieved from databases, such as Science Direct, SciFinder, PubMed (National Library of Medicine), Scopus, Wiley, American Chemical Society, Springer, and Web of Science. Results: Plants from the genus Millettia contain more than 400 different flavonoids, among which approximately 100 flavonoids were pharmacologically active in in vitro or in vivo studies. These flavonoids exhibited antioxidant, antiprotozoal, anti-inflammatory, and anticancer activities, among others. Conclusion: Flavonoids from Millettia plants were reported to exhibit in vitro antioxidant, antiprotozoal, anti-inflammatory, anticancer activities, etc. These compounds can be used as a starting point for the development of new agents against multifactorial diseases. However, more in vivo experiments, cytotoxicity tests, and detailed mechanism of action of Millettia bioactive flavonoids should be investigated.
Keywords: Millettia sp